Effects Of Synthesis Methods And Parameters On Sodium Zirconate For High-Temperature Co2 Sorption - Ooi, Khim May (2015)
Carbon dioxide (CO2) emission is among the causes of global warming. CO2 capture by CO2 adsorption has been one of the methods to reduce CO2 emission. Moreover, an adsorbent with high efficiency is needed for high-temperature CO2 capture from industrial hybrid processes. Sodium zirconate (Na2ZrO3) is one of the potential solid sorbents with high and stable cyclic CO2 sorption performance, but CO2 adsorption capacity closer to its ideal capacity is still desired. Furthermore, the effects of different methodologies on its CO2 capture performance were not reported previously. The main aim of this research work is to improve the synthesis and thus CO2 capture capacity of Na2ZrO3 for high-temperature CO2 sorption. Effects of carbonation and calcination conditions, different sodium (Na) precursors, and addition of citric acid (CA) and ethylene glycol (EG) on high-temperature CO2 sorption performance of synthesised Na2ZrO3 were investigated. Characterisation and CO2 sorption performance of samples were tested using thermogravimetric analysis, X-ray diffraction, N2 adsorption and SEM. All the above-mentioned parameters significantly affect the CO2 adsorption performances of the prepared Na2ZrO3 sorbents. The use of different Na precursor and CO2 adsorption temperature influenced the CO2 adsorption capacity of the samples. Different calcination conditions also affected the purity of Na2ZrO3. Addition of CA and EG resulted in producing purer Na2ZrO3 with more porous morphology and hence better regeneration stability than the sample prepared without the addition of CA and EG. The best CO2 adsorption capacity of 4.902 mmol CO2/g Na2ZrO3 was achieved at carbonation temperature of 550 °C, for the sample synthesised with sodium citrate as the Na precursor and CA:EG molar ratio of 2:1, and calcined at 900 °C for 4 h. Hence, this sorbent is suitable for high-temperature CO2 capture. It is recommended to test the functionality of this improved Na2ZrO3 sorbent under industrial conditions.